A Comparative Study of Kafka and NATS - Salonen, Nino (My University, 2025)
Distributed messaging systems are a key component of modern software architectures. This thesis compares two such systems to identify the differences and trade-offs between them. These results aim to help practitioners select the most suitable messaging system for their specific needs. Kafka is widely used in data-intensive applications for high throughput and persistent messaging, while NATS has traditionally focused more on lightweight real-time communication. With the addition of the JetStream persistence layer, NATS now has capabilities for message durability and replay, making it a viable alternative to Kafka. This thesis consists of a literature review and an empirical benchmark. The literature review explores the architectural differences and feature sets of both systems for event streaming. The benchmark measures latency, throughput, and resource usage while sending messages in both a single-node and a three-node environment with increased persistence. The results show that Kafka's design and features for high throughput enable it to achieve overall better performance while also using resources more efficiently. This advantage is more evident under heavy distributed workloads. NATS requires significantly less configuration effort and offers greater flexibility, while also performing reasonably well compared to Kafka. The findings indicate that Kafka's main strength is handling large volumes of messages, while NATS is a viable and more flexible alternative when maximum throughput is not the primary goal.
Keywords: messaging middleware, Kafka, NATS, event streaming, distributed systems